Metalloproteinase inhibitors in snakebite envenomations - Gutiérrez, José María (1999)
Pit viper envenomations are characterized by prominent local tissue damage, such as necrosis, hemorrhage and inflammation. These effects are relatively difficult to neutralize with antivenoms because of their rapid onset and development1. When treatment is delayed, as often occurs in tropical regions of the world, patients are at risk of developing permanent sequelae such as tissue loss or dysfunction. Horse- or sheep-derived antivenoms continue to be the mainstay in the treatment of snakebite envenomations, as they effectively neutralize systemically acting venom toxins, and partially decrease the extent of venom-induced local tissue damage. However, there is a need to develop ancillary treatments to inhibit locally acting toxins that could be used in addition to immunotherapy. Metalloproteinases are widely distributed in crotaline and viperine snake venoms2. They play a significant role in local tissue damage by inducing hemorrhage, oedema, myonecrosis, dermonecrosis and inflammation. Inhibitors of venom metalloproteinases, which could be injected directly at the site of venom injection, could offer a means of addressing this problem.